Jovem conectado: influências identitárias - Gonçalves, Luis Fernando [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The changes in contemporary society have been analyzed by various disciplines in the field of Humanities, trying to understand its implications for individuals and their social relationships. Here are some possible theoretical links between the concepts identity and seek to relate them to the main influences and outcomes observed in the identity influences young people from a specific region of São Paulo State process, always considering the contemporary social scene. We discuss from different social theories and their linkage with the concept of identification, emphasizing its procedural dimension. Because we understand that work in contemporary capitalism, assumes settings such as flexibility, temporality, precariousness, informality, producing changes that are expressed in the mode of being of workers, we believe that young people online will suffer from the same identity influences. Our reflections on the contemporary production context lead us to say that, despite the difficulties, the construction of identity processes in the subjects still takes place. Surely positions are transitory and ephemeral subjects, but you can not deny the coherence and continuity in the life history of each. We try to baste the data collected from questionnaires and focus analysis, a media room, and from this we find evidence to suggest such identity constructions, always supported the point of view of the young connected, which is the focus of our attention and study. Thus, we realize that we are facing another cultural sketch that reveals the strength of human relationships, be they virtual or real: the influence of identity is revealed in these kids connected as a direct and relevant to their existence in the Contemporary World production. This demonstrates the power of social networks in the formation of man, and more than that, points to current and innovative directions that deserve attention and assertive looks of educators, parents and leaders

As transformações da sociedade contemporânea vêm sendo analisadas por diversas disciplinas no campo das Ciências Humanas, buscando compreender suas implicações para os sujeitos e suas relações sociais. Apresentamos aqui algumas articulações teóricas possíveis entre os conceitos identidade e buscamos articulá-los com as principais influências e resultados observados no processo de influências identitárias de jovens de uma região específica do Estado de São Paulo, sempre considerando o cenário social contemporâneo. Buscamos discutir a partir de diferentes teorias sociais e da articulação com o conceito de identificação, enfatizando sua dimensão processual. Por entendermos que o trabalho, no capitalismo contemporâneo, assume configurações como flexibilidade, temporariedade, precariedade, informalidade, produzindo alterações que se expressam no modo de ser dos trabalhadores, acreditamos que os jovens conectados venham a sofrer de iguais influências identitárias. Nossas reflexões sobre o contexto produtivo contemporâneo nos levam a afirmar que, apesar das dificuldades, a construção dos processos identitários pelos sujeitos ainda tem lugar. Certamente são posições de sujeitos transitórias e efêmeras, mas não é possível negar a coerência e a continuidade na história de vida de cada um. Tentamos alinhavar os dados coletados em questionários e na análise focal, num ambiente midiático, e, a partir disto, localizar elementos que indiquem tais construções identitárias, sempre apoiados no ponto de vista do jovem conectado, que é nosso foco de atenção e de estudo. Desta maneira, percebemos que estamos diante de um outro esboço cultural que revela a força das relações humanas, quer sejam elas virtuais ou reais: a influência identitária é revelada nestes jovens conectados como uma produção direta e relevante para sua existência no Mundo Contemporâneo. Isso demonstra a força das redes sociais na...
Keywords: Sociology; Sociologia; Identidade (Psicologia); Identidade social; Redes sociais; Sociedade de consumo; Mídia digital; Territorialidade humana; Jovens; Mídia social; Internet - Aspectos sociais; Internet e adolescentes